Phylogenetic Analysis of Polynesian Ritual Architecture Suggests Extensive Cultural Sharing and Innovation - Cochrane, Ethan E (Waka Kuaka, 2015)
Ritual architecture across Polynesia displays similarities that are evidence of populations’ shared ancestry and interaction. Examination of ritual architecture traits—the design of courtyards, the use of uprights and sacrificial pits, the placement of walls and altars—has, for well over a century, contributed to hypotheses concerning the relatedness of different Polynesian groups and the transmission of ritual behaviours across islands and archipelagos. The research presented here follows this tradition and considers these traits from a quantitative phylogenetic perspective designed to generate hypotheses about the cultural relatedness of ritual architecture classes. Cladistics, a technique specifically designed to arrange classes into hierarchical patterns of relatedness, is presented and then used to construct cultural phylogenies of 198 pieces of ritual architecture from across East Polynesia. The cladistic analyses produce only very limited support for specific phylogenetic relationships between island and archipelago populations and instead suggest Polynesian ritual architectural variation is a product of both extensive horizontal cultural transmission or sharing and high levels of architectural trait innovation.